Linkage between theory‐based measurement of organizational readiness for change and lessons learned conducting quality improvement–focused research. Issue 2 (10th October 2016) - Jackson, George L.; Roumie, Christianne L.; Rakley, Susan M.; Kravetz, Jeffrey D.; Kirshner, Miriam A.; Del Monte, Pamela S.; Bowen, Michael E.; Oddone, Eugene Z.; Weiner, Bryan J.; Shaw, Ryan J.; Bosworth, Hayden B.
Abstract: Organizations have different levels of readiness to implement change in the patient care process. The Hypertension Telemedicine Nurse Implementation Project for Veterans (HTN‐IMPROVE) is an example of an innovation that seeks to enhance delivery of care for patients with hypertension. We describe the link between organizational readiness for change (ORC), assessed as the project began, and barriers and facilitators occurring during the process of implementing a primary care innovation. Each of 3 Veterans Affairs medical centers provided a half‐time nurse and implemented a nurse‐delivered, telephone‐based self‐management support program for patients with uncontrolled hypertension. As the program was starting, we assessed the ORC and factors associated with ORC. On the basis of consensus of medical center and research partners, we enumerated implementation process barriers and facilitators. The primary ORC barrier was unclear long‐term commitment of nursing to provide continued resources to the program. Three related barriers included the need to address: (1) competing organizational demands, (2) differing mechanisms to integrate new interventions into existing workload, and (3) methods for referring patients to disease and self‐management support programs. Prior to full implementation, however, stakeholders identified a high level of commitment to conduct nurse‐delivered interventions fully using their skills. There was also a significant commitment from the core implementation team and a desire to improve patient outcomes. These facilitators were observed during the implementation of HTN‐IMPROVE. As demonstrated by the link between barriers to and facilitators of implementation anticipated though the evaluation of ORC and what was actually observed during the process of implementation, this project demonstrates the practical utility of assessing ORC prior to embarking on the implementation of significant new clinical innovations.